SEMARANG RAGAM INSPIRASI DALAM MEMPERINGATI HARI ANAK NASIONAL KOTA SEMARANG 2020 (TALKSHOW, RAGAM LOMBA ANAK, PENTAS SENI DARING, WEBINAR, KONSER AMAL, DONASI) SEBAGAI MANAJER KREATIF DAN KOORDINATOR LOMBA - Laila Prativa Myranti; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
National Children's Day is the day the rights of Indonesian children are fulfilled, both for children residing in Indonesia and for children outside Indonesia. So that children in Indonesia get the same and broadest opportunity to be able to express themselves in positive activities. This year's National Children's Day will be held online, due to conditions that are currently experiencing the Covid-19 pandemic. Semarang City has also participated in celebrating National Children's Day by holding a series of activities in the form of talk shows, competitions, webinars, online art performances, charity concerts, and donation submissions. The theme of this event was